Plant Functional Types of Woody Species Related to Fire Disturbance in Forest-Grassland Ecotones - Müller, Sandra C; Overbeck, Gerhard E; Pfadenhauer, Jörg; Pillar, Valério D (Plant ecology, 2007)
The study of plant functional types (PFTs) has been widely emphasized when analysing plant community changes in relation to variations in climate and disturbance regime. In this study, we search for PFTs of woody species near forest-grassland boundaries in South Brazil where, due to climate, forests tend to expand over grassland but are being restricted by frequent fires. We aimed at answering the questions: (i) which plant functional types of forest woody species can establish in adjacent grassland subject to fire disturbance and (ii) which plant functional types of forest and grassland woody species are related to short-term community dynamics in frequently burned grassland. Traits were assessed in woody plants in 156 plots (6.75 m²) arranged in 12 transects across forest-grassland boundaries with different fire history in their grassland part. The analysis used a recursive algorithm to search for traits and PFTs maximally associated to spatial distance from forest limit in one analysis, and elapsed time since last fire in another. As a result, nine PFTs of forest woody species were identified that best described community patterns associated to distance from forest. Resprouting ability characterized forest plants able to colonize grasslands. PFT diversity was higher in border plots than inside forest or grassland. Four PFTs of forest and grassland woody species best described woody species community patterns in the grassland associated to elapsed time since fire. Taller individuals of single-stemmed shrubs predominated in late post-fire recovery (3-4 years), while shorter multi-stemmed shrubs in recently burned areas (3 months to 1 year). PFTs of forest trees occurred in border plots or, as established adults, in grassland, remaining unaffected by fire. We conclude that easily measurable structural plant traits, such as those used in our study, are sufficient to evaluate post-fire community dynamics. Forest PFTs in burned grassland are restricted to those with resprouting ability to survive recurrent fire events. Establishment success is highest on protected sites with lesser or low-intensity fire.